A bi-planar coil system for nulling background magnetic fields in scalp mounted magnetoencephalography - Holmes, Niall; Leggett, James; Boto, Elena; Roberts, Gillian; Hill, Ryan M.; Tierney, Tim M.; Shah, Vishal; Barnes, Gareth R.; Brookes, Matthew J.; Bowtell, Richard (NeuroImage (Orlando, Fla.), 2018)
Small, commercially-available Optically Pumped Magnetometers (OPMs) can be used to construct a wearable Magnetoencephalography (MEG) system that allows large head movements to be made during recording. The small dynamic range of these sensors however means that movement in the residual static magnetic field found inside typical Magnetically Shielded Rooms (MSRs) can saturate the sensor outputs, rendering the data unusable. This problem can be ameliorated by using a set of electromagnetic coils to attenuate the spatially-varying remnant field. Here, an array of bi-planar coils, which produce an open and accessible scanning environment, was designed and constructed. The coils were designed using a harmonic minimisation method previously used for gradient coil design in Magnetic Resonance Imaging (MRI). Six coils were constructed to null Bx, By and Bz as well as the three dominant field gradients dBx/dz, dBy/dz and dBz/dz. The coils produce homogeneous (within ±5%) fields or field gradients over a volume of 40 × 40 × 40 cm3. This volume is sufficient to contain an array of OPMs, mounted in a 3D-printed scanner-cast, during basic and natural movements. Automated control of the coils using reference sensor measurements allows reduction of the largest component of the static field (Bx) from 21.8 ± 0.2 nT to 0.47 ± 0.08 nT. The largest gradient (dBx/dz) was reduced from 7.4 nT/m to 0.55 nT/m. High precision optical tracking allowed experiments involving controlled and measured head movements, which revealed that a rotation of the scanner-cast by ±34° and translation of ±9.7 cm of the OPMs in this field generated only a 1 nT magnetic field variation across the OPM array, when field nulling was applied. This variation could be further reduced to 0.04 nT by linear regression of field variations that were correlated with the measured motion parameters. To demonstrate the effectiveness of the bi-planar coil field cancellation system in a real MEG experiment, a novel measurement of retinotopy was investigated, where the stimulus remains fixed and head movements made by the subject shift the visual presentation to the lower left or right quadrants of the field of view. Left and right visual field stimulation produced the expected responses in the opposing hemisphere. This simple demonstration shows that the bi-planar coil system allows accurate OPM-MEG recordings to be made on an unrestrained subject. •The design and use of bi-planar coils for magnetic field nulling is described.•Field nulling allows large subject movements during onscalp MEG recordings.•Optical tracking shows high quality data can be acquired during these movements.•A novel measurement of retinotopy where the subject moves their head is shown.